A COMPARATIVE ANALYSIS OF EMOTIONAL AND COGNITIVE LOAD IN OFFENSIVE AND DEFENSIVE KHO-KHO PLAYERS - Sangeetha .K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kho-Kho is a traditional Indian sport that demands a combination of speed, agility, strategy, and mental resilience. The game consists of two teams taking turns to attack (chasing) and defend (running), making it a high-intensity sport that imposes both emotional and cognitive stress on players. The current study aims to analyze and compare the emotional and cognitive load experienced by offensive (runners) and defensive (chasers) Kho-Kho players during competitive play. Emotional load refers to stress, anxiety, and psychological pressure, while cognitive load involves decision-making, reaction time, and strategic thinking. A total of 80 elite Kho-Kho players(male and female) participated in the study. Physiological (heart rate variability, salivary cortisol levels) and psychological (self-report questionnaires, cognitive assessments) data were collected before, during, and after matches. The results indicate that offensive players experience higher emotional stress due to the continuous threat of being tagged, while defensive players endure higher cognitive stress due to strategic planning and tracking multiple opponents. The findings highlight the need for sport-specific mental training programs tailored to the unique psychological demands of offensive and defensive roles. The study contributes to sports psychology by emphasizing the interplay of cognitive and emotional load in high-intensity team sports like Kho-Kho and suggests practical interventions for optimizing player performance.